Análisis de la propuesta de integración de méxico con mic (middle america cluster) y recomendación para la ubicación de la jefatura regional - Alexander Yépez, Nino (2010)
Since the beginning of 2008 Maersk Line has decided to decentralize its regional offices under the process known as Streamline which is defined as the company gets closer to customers through the power of decision by the sales force in order to reduce the bureaucratic structure to hold shares in the market much faster. As a result of the Latin American initiative that included all countries from Mexico to Argentina was divided into six subregions Brazil, River Plate (Argentina, Uruguay and Paraguay), WCSA (Chile, Peru, Ecuador), MIC (Guatemala, Honduras, El Salvador, Nicaragua, Belize), Mexico and CAR (Panama, Colombia, Venezuela, Costa Rica and the Caribbean islands). The criterion for the definition of the subregions was based on common denominators of culture, location and synergies in the field of shipping products and services that are shared among countries within the subregion. The proposed integration of Mexico and MIC is focused on cost reductions, primarily from the reduction of one of the senior management team, as a fact that the Mexican business has developed in an important way for industrial economies levels, indicating a number of specialists and managers can be found in various cities in Mexico.